Report on the legal situation of homosexual men and women in the armed forces. - Elsen, Casimir ([S.l.] : ILGA, 1987)
Fonds Suzan Daniel (FSD)
Engels
Monografie
Keywords: homoseksualiteit; lesbische vrouwen; militairen